TRANSMISSION-TRANSFORMATION OF MURATTAL AND MUJAWWAD OF THE QUR’AN IN THE DIGITAL ERA: AN ANALYSIS OF AHMAD RAFIQ’S LIVING QUR’AN - Rais Nasruddin, M. (International Journal of Multidisciplinary Reseach, 2026)
The number of murattal and mujawwad of the Qur’an applications today result in different transmission and transformation before the entry of the digital era. This shows one of the phenomena of the Qur’an that "lives" in society, or is called the Living Qur’an. The study of Ahmad Rafiq’s Living Qur’an provides idea about the transmission-transformation of knowledge and practice. Through Ahmad Rafiq’s Living Qur’an, this article aims to examine the phenomenon of murattal and mujawwad of the Qur’an, and its transmission and transformation since the time of the Prophet Muhammad until the digital era. This article is a study of the Living Qur’an that uses the descriptive-analytical method in its analysis. This article concludes that the position of the Qur’an in the murattal and mujawwad phenomena is not only as an object but also as a subject that actively raises the practice of murattal and mujawwad reading style. This phenomenon describes the form of performative reception of the Muslim community towards the Qur’an. The transmission murattal and mujawwad of the Qur’an that occurs in the digital era are no longer only in the category of teachers and students, but also in the form of a discursive tradition. Meanwhile, the transformation is that murattal and mujawwad al-Qur’an are no longer only heard directly when religious activities are held, but can also be listened anytime and anywhere through digital applications that provide murattal and mujawwad of the Qur'an